Fifteen-minute consultation: Insulin pumps for type 1 diabetes in children and young people. Issue 3 (3rd January 2018) - Prentice, Philippa; Elleri, Daniela
Abstract : There is increasing worldwide use of continuous subcutaneous insulin infusions in paediatric type 1 diabetes (T1D), reflecting recent research outcomes and guidance, as well as families' wishes. Children/young people may present acutely with medical or surgical problems, in addition to issues related to T1D. This review provides general paediatricians with an introduction to pump therapy, highlighting common problems, management issues and when to seek specialist advice.